Adaptive capacity of Arctic communities in the context of climate change and shipping growth: A review of Russian and Western literature. (2020) - Olsen, Julia
Abstract: Throughout the past two decades, the number of studies examining the adaptive capacity of Arctic communities in the context of climate change has been increasing; however, little is known about Arctic communities' ability to adapt to certain emerging changes, such as increased shipping activity. To address this knowledge gap, this study systematically analyses published scientific articles on community adaptive capacity in circumpolar Arctic, including articles published in Russian which may not be captured in English-only reviews. Throughout this review, the study focuses on three areas: the development of the adaptive capacity framework; the conditions that enable community adaption abilities; and the extent to which shipping developments are addressed in the literature. This study demonstrates that the adaptive capacity framework has been significantly developed both theoretically and methodologically and is broadly used to address new types of climatic and non-climatic changes. Though the impacts from the shipping development are discussed in some studies, there is a clear need for further examination of coastal communities' ability to adapt to such changes. Additionally, the study reveals limitations in the application of the Western conceptual terminology when exploring community-based research by Russian scholars.